Life After Life : The Investigation of a Phenomenon, Survival of Bodily Death - Moody, Raymond A.; Preface by Melvin Morse and Foreword by Elisabeth Kubler Ross (London Rider, 2001)
Fascinating and eminently readable this book is a groundbreaking study of more than 100 people who have experienced clinical 'death' and survived.
Keywords: Parapsychology -- Reincarnation -- Reincarnation therapy